2022
DOI: 10.1038/s41419-022-05185-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of the novel tyrosine kinase inhibitor DCC-2036 on triple-negative breast cancer stem cells through AXL-KLF5 positive feedback loop

Abstract: Triple-negative breast cancer (TNBC), an aggressive histological subtype of breast cancer, exhibits a high risk of early recurrence rate and a poor prognosis, and it is primarily associated with the abundance of cancer stem cells (CSCs). At present, the strategies for effectively eradicating or inhibiting TNBC CSCs are still limited, which makes the development of novel drugs with anti-CSCs function be of great value for the treatment of TNBC, especially the refractory TNBC. In this study, we found that the sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It activates the expression of NANOG and FGFBP1 in TNBC, which are required for the maintenance of the cancer stem cell (CSC) population [ 28 , 38 ]. Pharmaceutical inhibition of KLF5 could significantly suppress the CSC properties of TNBC and enhance chemotherapy responses [ 39 , 40 ]. KLF5 can directly bind to the 5’ regulatory region of EGFR and enhance its transcription [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It activates the expression of NANOG and FGFBP1 in TNBC, which are required for the maintenance of the cancer stem cell (CSC) population [ 28 , 38 ]. Pharmaceutical inhibition of KLF5 could significantly suppress the CSC properties of TNBC and enhance chemotherapy responses [ 39 , 40 ]. KLF5 can directly bind to the 5’ regulatory region of EGFR and enhance its transcription [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through its capacity to stimulate oncogenic PI3K‐AKT‐mTOR, MAPK, JAK‐STAT and SRC‐FAK signaling, AXL can sustain aberrant stem cell renewal, epithelial‐to‐mesenchymal transition (EMT), immune evasion and cancer cell invasion 48,49 . Particularly in normal and tumor cells of the mammary gland, AXL was frequently shown to play a critical role in the maintenance of stem cell properties 48,50‐52 . Inline, several reports suggested an implication of the AXL signaling in drug‐resistant phenotypes of TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Particularly in normal and tumor cells of the mammary gland, AXL was frequently shown to play a critical role in the maintenance of stem cell properties. 48,[50][51][52] Inline, several reports suggested an implication of the AXL signaling in drug-resistant phenotypes of TNBC. Wilson et al identified R428 synergizing with antimitotic agents in resistant cell lines.…”
Section: Discussionmentioning
confidence: 99%